One-Pot Synthesis of Benzo[4,5]imidazo[1,2-a]pyrimidine Derivatives Using Melamine Trisulfonic Acid as Catalyst - Shang, Xiaojun; Geng, Mingjiang; Wu, Liqiang (Asian Journal of Chemistry, 2011)
Melamine trisulfonic acid catalyzes efficiently the one-pot condensation of 2-aminobenzimidazole, aldehyde and b-dicarbonyl compounds under solvent-free conditions to afford the corresponding benzo[4,5]imidazo[1,2-a]pyrimidine derivatives in single step. This new approach consistently has the advantage of excellent yields (86-95 %) and short reaction times of 4-6 h. The catalyst can be recovered and recycle.